Luteinizing hormone release and plasma metabolites in mature, ovariectomized beef cows fed various lipid diets - Peters, C.W.; Corah, L.R.; Cochran, R.C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feeding rumen-escape lipid or soybean oil in a range supplement to beef cow resulted in elevated blood cholesterol and enhanced luteinizing hormone (LH) release compared to a control (milo and soybean meal) supplement. Cholesterol was elevated (P<.01) within 14 d of lipid feeding. The amplitude of each LH pulse and maximal pulse height were greater (P<.05) when cows were fed high-lipid diets. The positive influence of high-lipid diets on reproductive function may be explained in part by enhanced LH release.
Keywords: Beef; Beef cows; Lipid; Luteinizing hormone; Cholesterol; Reproduction